Kontribusi Mahasiswa dalam Membentuk Karakter Melalui Pendidikan Seni Tari Tradisional Se-Kabupaten Serang - Oktaviani, Anna Maria; Aris, Ika Evitasari; Gunardi, Ari (MULIA (Jurnal Pengabdian kepada Masyarakat), 2024)
Character education and introduction to dance is one of the beginnings of planting and forming the character of students through character building training. Character values should need to be taught to students as successors to the nation's generation. However in the current era, students do not understand the values of character and even behave incorrectly in the environment. Providing character education coaching can be associated with linking the provision of training for students which can lead to the introduction of the nation's culture. This training aims to improve the character of students through dance training that can introduce dance culture at the same time so that students can provide knowledge of the nation's culture discussion methods and demonstration methods. The results of this service are that improving the character education of students who are delivered other than the delivery of material related to character and some examples of the application of good character values.